Rare earth extraction from wet process phosphoric acid by emulsion liquid membrane - 张利昌 陈前林 康超 马昕 杨尊良 (Journal of rare earths, 2016)
The recovery of rare earths （RE） during the wet processing of phosphoric acid is very important, the method of emul- sion liquid membrane （ELM） with di（2-ethylhexly） phosphate （D2EHPA） as carrier has the high selectivity while cannot provide a satisfactory extraction rate. Here novel method of emulsion liquid membrane （ELM） using Aniline as carrier to extract RE from the feed solution was proposed. The method could increase the extraction rate of RE in the real sample to 93%. The effects of dif- ferent parameters such as type and concentration of carrier and surfactant, hydrochloric acid concentration, organic to internal phase volume ratio, membrane to external phase volume ratio on extraction of RE3＋ were investigated. Quantitative extraction （〉93%） of RE3＋ was observed with 6 vol.% Aniline and 4 vol.% T 154 liquid membrane at external to internal phase volume ratio of 10 for the feed solution. The proposed method of ELM using Aniline as carrier can be expected to provide a practical, efficient, and economical method for extracting RE from phosphate leach solution with high acidity in the industry of wet process phosphoric acid.